CONNECTION MODEL OF CONCRETE FILLED STEEL TUBE (CFT) COLUMN TO STEEL BEAM UNDER CYCLIC - Agustina Dwi Atmaji; Budi Suswanto; Endah Wahyuni (Journal of Civil Engineering, 2019)
Various types of structural technology began to develop rapidly, one of which was composite steel. Composite steel (Concrete Filled Steel Tube) is a structure consisting of two or more materials with different material properties and form one unit so as to produce better combined properties. Compared to conventional steel, this column has many advantages such as convenient formwork for concrete cores provided by steel tubes, increased strength and good ductility. This study uses the CFT column as the main variable by considering variations in the CFT column on the connection using ABAQUS. Modeling was carried out with a test object of 203 × 133 × 7.8 × 5.8 mm and the CFT column dimensions of rectangular 220 × 220 × 6 mm, and circular Ø 220 mm t = 8 mm. The research method uses two steps static-general method with static-risk. The results of these two research methods have the results of approaching and having the same behavior. Modeling has fulfilled the requirements of modeling the column-beam joints that can be used in a system of earthquake-resistant reinforced steel composite concrete frame structures. Based on the modeling results that have been done, modeling has fulfilled the connection that has sufficient ductility capability.